Phylogenetic analysis of selected cyprinids inferred from sequencing of a mitochondrial cytochrome c oxidase I (COI) gene - Esa, Yuzine B.; Siraj, Siti Shapor; A. Rahim, Khairul Adha; Daud, Siti Khalijah; Guan, Tan Soon (Journal of Tropical Biology & Conservation (JTBC), 2016)
This study examines the phylogenetic relationships of 21 selected freshwater cyprinids using sequence analysis of mitochondrial DNA cytochrome c oxidase I (COI) gene (464 base pairs).Â 